Vulnerability to winter mortality in elderly people in Britain: population based study. Issue 7467 (17th August 2004) - Wilkinson, Paul; Pattenden, Sam; Armstrong, Ben; Fletcher, Astrid; Kovats, R Sari; Mangtani, Punam; McMichael, Anthony J
Abstract: Objective To examine the determinants of vulnerability to winter mortality in elderly British people. Design Population based cohort study (119 389 person years of follow up). Setting 106 general practices from the Medical Research Council trial of assessment and management of older people in Britain. Participants People aged ≥ 75 years. Main outcome measures Mortality (10 123 deaths) determined by follow up through the Office for National Statistics. Results Month to month variation accounted for 17% of annual all cause mortality, but only 7.8% after adjustment for temperature. The overall winter:non-winter rate ratio was 1.31 (95% confidence interval 1.26 to 1.36). There was little evidence that this ratio varied by geographical region, age, or any of the personal, socioeconomic, or clinical factors examined, with two exceptions: after adjustment for all major covariates the winter:non-winter ratio in women compared with men was 1.11 (1.00 to 1.23), and those with a self reported history of respiratory illness had a winter:non-winter ratio of 1.20 (1.08 to 1.34) times that of people without a history of respiratory illness. There was no evidence that socioeconomic deprivation or self reported financial worries were predictive of winter death. Conclusion Except for female sex and pre-existing respiratory illness, there was little evidence for vulnerability to winter death associated with factors thought to lead to vulnerability. The lack of socioeconomic gradient suggests that policies aimed at relief of fuel poverty may need to be supplemented by additional measures to tackle the burden of excess winter deaths in elderly people.